American first before anything else - Abd Razak, Dzulkifli (2008)
THE world appears very excited that Barack Obama is the presidentelect of the United States of America. Added to this is, of course, the exuberance that marks the end of what arguably is the worst presidential period under the Bush administration. Many are hopeful that Obama will be the torch to brighten the darkness that has encapsulated the White House for the last eight years. That Obama is the first "black" president to occupy the White House is to most no longer a contradiction, especially to the younger voters who are mainly responsible for the choice.